Research Gap Strategies in the Introduction Section of Local Journal Articles in the Field of Language Teaching and Literature - Jamaludin Jamaludin; Dian Eka Chandra Wardhana; Safnil Arsyad; Ade Hidayat (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2026)
Research gap statement in the introduction section of a research article is very crucial in order to engage and attract readers to read the article further. Previous studies have found several ways of research gap employed by authors; however, these studies have not fulfilled all aspects, especially regarding the research gap strategy in the field of Indonesian Language Teaching and Literature. Therefore, this research fills this gap by describing the authors’ strategy in presenting the research gap and its linguistic features in the introduction sections of articles published in nationally accredited journals. The data were fifty articles written by Indonesian authors, randomly selected from nationally accredited journals in the field of Indonesian Language Teaching and Literature. The data were analyzed using content analysis with qualitative design. The findings of the study show that there was a tendency for Indonesian authors to present research gap in the introduction section by suggesting solution to the research problem. This strategy is addressed by using particular linguistic features, such as phrases indicating the need for further study on the topic under investigation and phrases suggesting recommendations, which emerged as the two most frequently used expressions. The implication of these findings is the development of a deeper understanding of research gap writing strategies by Indonesian new authors is beneficial before composing academic texts for scientific publication such as research articles published in journals.